Analisis Pengaruh Nilai Tukar Dolar Amerika Serikat, Inflasi, Dan Produksi Terhadap Ekspor Ikan Hias Provinsi Jawa Timur - Andrianto, Muhammad Dwi; S, Ririt Iriani (Universitas Batanghari, 2024)
This study aims to determine and analyze the effect of the United States dollar exchange rate, inflation, and production on ornamental fish exports in East Java province. The researchers' strategy for this study is quantitative research, and they use statistical formulas to aid in the analysis of the data and information collected. The information used in this study is a subset of secondary data collected from organizations or organizations related to it and then reprocessed. The Central Bureau of Statistics of East Java and the Ministry of Marine Affairs and Fisheries are the organizations involved in this research. The Ministry of Marine Affairs and Fisheries of East Java and the Central Bureau of Statistics are the organizations involved in this research. Documentation, or finding information about a subject or variable in the form of notes, books, papers or articles, journals, etc., is a strategy used to collect data for the study. Ordinary Least Squares (OLS) conducted using SPSS software is an analytical technique used to assess the impact of the US dollar exchange rate, inflation, and production on ornamental fish exports in East Java Province. The results of this study show that the BLUE test conducted on export variables has no correlation, statistical analysis shows that simultaneously exchange rate variables, inflation, production affect ornamental fish exports, partial analysis reveals that exchange rates have little influence on ornamental fish exports, partial analysis shows that ornamental fish exports are significantly positively affected by inflation. Partial analysis on ornamental fish production has a significant impact on ornamental fish exports.